Editorial - Bhalalusesa, Eustella (Papers in Education and Development, 2024)
It is with great pleasure that I welcome you to Volume 42, Issue 2 of Papers in Education and Development (PED), an issue teeming with thought-provoking research that offers timely reflections on some of the most pressing issues shaping education and development in Africa and beyond. The eleven articles presented in this issue engage in wide-ranging conversations around youth development, teacher education, inclusive schooling, skills acquisition, and institutional responsiveness. What emerges is not only a mosaic of rich research contributions but also a reflective mirror of contemporary educational realities across diverse contexts. As we navigate an era marked by rapid technological changes, socio-economic inequalities, and shifting labour market demands, the role of education in cultivating relevant competencies, inclusive practices, and institutional resilience has never been more critical. The articles in this issue converge around four overarching themes: youth empowerment and employability, inclusive and differentiated pedagogies, assessment practices, teacher development, and deployment policies and resilience and crisis management in schools. Each theme contributes to a broader discourse on how education systems can both be strengthened to address today’s challenges and reimagined to foster equity, inclusion, employability, resilience, and sustainability.